THE EXPERIMENTAL MODEL OF DISC-PUMP FOR MECHANICAL CIRCULATORY SUPPORT - A. M. Chernyavskiy; T. M. Ruzmatov; A. V. Fomichev; A. E. Medvedev; Y. M. Prikhodko; V. M. Fomin; V. P. Fomichev; V. P. Chekhov (Вестник трансплантологии и искусственных органов, 2017)
The relevance of the use of circulatory support systems for the treatment of chronic heart failure (CHF) has increased over the recent years. Up to 20% of the patients from the waiting list for a donor heart die each year before they could get one. In our country, there is a huge need for mechanical heart support systems. However, the acquisition of foreign systems is associated with the excessive fi nancial costs. In addition, nowadays, there is no system that would meet all medical and technical requirements in full, and at the same time, would be of high safety for the patient. Therefore, research on the development of the systems of auxiliary circulation is highly relevant and is in demand in our country. One of the promising directions in this fi eld is disk pumps of viscous friction, which are based on the operation principle of Tesla disk pump. This article describes the creation and operation of the current model of the disk pump. The results of the bench tests confirmed that the expendable pressure characteristics of our disk pump are capable of providing the necessary parameters of blood circulation. The findings confi rm the perspective of the selected research area and provide the basis for further development and testing of this model of pump.